Agricultural growth, rural development and poverty - Parthasarathy, G. (Visakhapatnam, 1988)
The volume contains writings of Prof. Parthasarathy over the last three decades on a theme close to his heart, 'Agricul tural Growth, Rural Development and Poverty'. Altogether there are 23 articles presented under eight sub-themes in this book. And, it contains the foreword by Prof. M.L. Dantwala, the doyen among the agricultural economists in India, besides a comprehensive list of Prof. Parthasarathy's research contri butions and the positions held and awards received by him over the years.
Keywords: Rural development-India